Determinants of Political Stability to Support Foreign Investment in Indonesia - Benny Budiawan Tjandrasa (Petra International Journal of Business Studies, 2021)
What investors often consider before deciding to invest in various countries is the political situation. The risks faced by investors in the event of political instability are regulatory changes, legal disputes, forced takeovers of companies, disruption to regional stability, policies against acts of terrorism, and changes in state ideology. The purpose of this study is to find a determinant of political stability in Indonesia that will be useful for investors and multinational companies, and the government in maintaining political stability. Systematic secondary data sampling from January 2015 to December 2019 was used for explanatory study purposes and to build a model. This study concludes that the rule of law, control of corruption, and oil prices have a significant effect on political stability in Indonesia, while the inflation rate does not have a significant effect on political stability in Indonesia. The novelty of this research is the formation of a political stability model for Indonesia and why an increase in control of corruption actually has a negative effect on political stability in Indonesia.